Mapping five repetitive DNA classes in sympatric species of Hypostomus (Teleostei: Siluriformes: Loricariidae): analysis of chromosomal variability - Pansonato-Alves, José Carlos [UNESP]; Serrano, Érica Alves [UNESP]; Utsunomia, Ricardo [UNESP]; Scacchetti, Priscilla Cardim [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Springer Nature, 2013)
Fish belonging to the genus Hypostomus are known for exhibiting a striking diversity in its karyotype structure, however the knowledge concerning the distribution patterns of heterochromatin and location of repetitive DNA sequences in the karyotypes is still limited. Aiming a better understanding of the chromosomal organization in this group, we analyzed three sympatric species of Hypostomus collected in the Hortelã stream, a component of the Paranapanema River basin, Botucatu/SP/Brazil. The analyses involved the cytogenetic characterization and chromosomal mapping of repetitive sequences and intra/interspecific comparisons using sequences of the cytochrome C oxidase subunit I. The results revealed that H. ancistroides presents a karyotype with 2n = 68 chromosomes, H. strigaticeps 2n = 72 chromosomes, and H. nigromaculatus 2n = 76 chromosomes. In addition to differences found in the diploid number, it was also observed variations in karyotypic formulae, amount of constitutive heterochromatin, and location of nucleolus organizer regions. The cytogenetic mapping of 5S and 18S rDNA, as well as of the H3 histone gene, disclosed a differential dispersion process among the three species. In some cases the Rex1 transposable element showed to be co-located with 5S rDNA sites. The molecular analyses support the cytogenetic data and represent an additional tool for the characterization of the analyzed species. The results evidenced that chromosomal variations are not restricted to differences in diploid number or karyotypic macrostructure in the genus Hypostomus, indicating that events such as transposition of heterochromatin and rDNA segments may participate in the differentiation process occurred in these species. © 2013 Springer Science+Business Media Dordrecht.
Keywords: H. ancistroides; H. nigromaculatus; H. strigaticeps; Histone; Mobile elements; rDNA